Chamber Tombs of Çerçili Necropolis and the Cult Area - İbrahim Üngör (Art-Sanat)
The district of İslâhiye is located in the eastern part of the Mediterranean Region, at the eastern foothills of the Amanos Mountains. This region, which is highly significant in terms of natural resources and strategically important, has hosted different cultures since ancient times. Settlements that began in the Paleolithic Age intensified after the Chalcolithic Age. This density continued throughout the Bronze Age, Iron Age, Middle Ages, and up to the present day. Some of the roads and passes that connect Syria and Anatolia, and are of great importance, pass through this region.The Çerçili Necropolis, which is the subject of this study, was first identified during surface surveys in 2009. The necropolis area was created by carving into the rocky slope at the eastern foothills of the Amanos Mountains, at the western end of the Çerçili district, located 5 km west of the İslâhiye district. The necropolis site contains chamber tombs with arcosolia, cult niches, and a levelled area within the burial area, which is believed to be a cult space, measuring 24 square meters. The investigation of the Çerçili Necropolis, as part of the surface surveys, aims to contribute to the research on the Roman period, burial typologies, and funeral traditions in the region.